1991
DOI: 10.1002/j.1460-2075.1991.tb04997.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat protein promotes formation of more-processive elongation complexes.

Abstract: The Tat protein of HIV‐1 trans‐activates transcription in vitro in a cell‐free extract of HeLa nuclei. Quantitative analysis of the efficiency of elongation revealed that a majority of the elongation complexes generated by the HIV‐1 promoter were not highly processive and terminated within the first 500 nucleotides. Tat trans‐activation of transcription from the HIV‐1 promoter resulted from an increase in processive character of the elongation complexes. More specifically, the analysis suggests that there exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
255
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(264 citation statements)
references
References 62 publications
(30 reference statements)
9
255
0
Order By: Relevance
“…One could therefore explain part of the synergism in transcriptional activation if interaction of acidic activators with TFIIH stimulates melting of the DNA at the promoter. This phenomenon would have been difficult to detect in vitro because acidic activators also stimulate formation of the closed preinitiation complex (65,112,114 18) and increasing the processivity of chain elongation by RNA polymerase 11 (52,54,61,71). Similarly, other typical activators, including VP16, may also generally stimulate chain elongation by RNA polymerase 11 (119).…”
Section: Discussionmentioning
confidence: 99%
“…One could therefore explain part of the synergism in transcriptional activation if interaction of acidic activators with TFIIH stimulates melting of the DNA at the promoter. This phenomenon would have been difficult to detect in vitro because acidic activators also stimulate formation of the closed preinitiation complex (65,112,114 18) and increasing the processivity of chain elongation by RNA polymerase 11 (52,54,61,71). Similarly, other typical activators, including VP16, may also generally stimulate chain elongation by RNA polymerase 11 (119).…”
Section: Discussionmentioning
confidence: 99%
“…The X nut site will function as a discrete element when moved away from its cognate promoter, whereas TAT-mediated antitermination requires TAR to be located immediately adjacent to the HIV promoter (Selby et al, 1989), and it also remains unclear whether TAT acts to overcome specific termination signals in the HIV TAR region in a manner analogous to the antitermination of the prokaryotic terminators. Most of the recent evidence suggests that in the absence of TAT, LTR-initiated transcription terminates at many, possibly random, downstream sites (Lapsia et al, 1989;Marciniak and Sharp, 1991;Kessler and Mathew, 1992). Marciniak and Sharp (1991) have suggested that in the absence of TAT, the distribution of RNA polymerases along an HIV LTRdriven gene in an in vitro system is such as would be predicted by the existence of two classes of elongation complex initiating from the HIV promoter.…”
Section: Regulation Of Transcriptional Elongation In Hiv Expressionmentioning
confidence: 99%
“…Most of the recent evidence suggests that in the absence of TAT, LTR-initiated transcription terminates at many, possibly random, downstream sites (Lapsia et al, 1989;Marciniak and Sharp, 1991;Kessler and Mathew, 1992). Marciniak and Sharp (1991) have suggested that in the absence of TAT, the distribution of RNA polymerases along an HIV LTRdriven gene in an in vitro system is such as would be predicted by the existence of two classes of elongation complex initiating from the HIV promoter. Most complexes are of the less processive unstable form and terminate transcription at a relatively uniform rate over the first 1000 bp of template; the less abundant form is more processive and stable and elongates through the several kilobases of template analyzed.…”
Section: Regulation Of Transcriptional Elongation In Hiv Expressionmentioning
confidence: 99%
“…Tat is able to stimulate elongation, in some cases without any apparent effect on initiation (31,33,40,47), whereas VP16 also strongly stimulates initiation. Tat is a unique activator because it is recruited to the transcription complex by binding to nascent RNA rather than to promoter DNA.…”
mentioning
confidence: 99%